Design of RAFT synthesized amphiphilic and stimuli-responsive block copolymers for encapsulation of polyphenols in polymersomes - Gomes, Catarina (2018)
This research is devoted to the design and synthesis of amphiphilic/stimuli-responsive block copolymers for encapsulation of polyphenols in polymersomes. The Reversible Addition- Fragmentation Chain Transfer (RAFT) polymerization technique is used to get tailored amphiphilic block copolymers. Multiple combinations between hydrophilic/hydrophobic monomers, RAFT agents and initial compositions are the main design variables of the synthesis runs. Experimental studies are guided by modeling tools to aid in the design of the materials (e.g. to specify the sizes of the two blocks, pH sensitivity). Isolated polyphenols (e.g. resveratrol, quercetin) and more complex extracts from different kinds of plants are afterwards encapsulated in polymersomes, aiming at the development of carriers for protection and controlled release of these bioactive compounds. It is shown that the produced aggregates have a long colloidal stability and are promising vehicles for the stimulatedrelease of polyphenols.